2020
DOI: 10.1016/j.bpj.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Tautomeric Effect of Histidine on β-Sheet Formation of Amyloid Beta 1–40: 2D-IR Simulations

Abstract: Histidine state (protonated or d or ε tautomer) has been considered the origin of abnormal misfolding and aggregation of b-amyloid (Ab). Our previous studies reported that the ddd isomer of Ab (1-40) has a greater propensity for b-sheet conformation compared to other isomers. However, direct proof of the tautomeric effect has not been reported. In this context, we calculated histidine site-specific two-dimensional infrared spectroscopy of the ddd, εεε, and ppp (all protonated histidine) systems within the fram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…The CHC//N-terminus and CHC//C-terminus were the interaction regions of the β-strand structures. Many reports are available on such three β-strand structures. , In contrast, in Aβ42 H6R, except Aβ42 (rδε), which is prone to a nondominant conformational feature, Aβ42 (rεε), Aβ42 (rεδ), and Aβ42 (rδδ) had dominant conformational properties with top conformational states of 73.2%, 67.0%, and 56.5%, respectively. Similarly, the CHC//N-terminus and CHC//C-terminus were the interaction regions.…”
Section: Resultsmentioning
confidence: 99%
“…The CHC//N-terminus and CHC//C-terminus were the interaction regions of the β-strand structures. Many reports are available on such three β-strand structures. , In contrast, in Aβ42 H6R, except Aβ42 (rδε), which is prone to a nondominant conformational feature, Aβ42 (rεε), Aβ42 (rεδ), and Aβ42 (rδδ) had dominant conformational properties with top conformational states of 73.2%, 67.0%, and 56.5%, respectively. Similarly, the CHC//N-terminus and CHC//C-terminus were the interaction regions.…”
Section: Resultsmentioning
confidence: 99%
“…28 In our earlier research, we revealed that Aβ40 monomers carrying the His6(δ)–His13(δ)–His14(δ) (the so-called δδδ isomeric form) and His6(π)–His13(π)–His14(π) isomer (πππ) leads to greater amounts of β-structure generation, as compared with the His6(ε)–His13(ε)–His14(ε) (εεε) tautomeric isomer. 29…”
Section: Introductionmentioning
confidence: 99%
“…21,22 Furthermore, we performed two-dimensional infrared (2D IR) analysis to characterize the H-bond and charge networks in a dipeptide model for different states of histidine tautomers. 23 On the basis of the theoretical studies, the histidine tautomerism hypothesis was proposed for protein misfolding. More relevant research is needed to verify and develop this hypothesis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Some isomers of peptides under histidine tautomeric effect are more toxic relative to wild type. Because of the importance of oligomers in the misfolding of Aβ proteins, we investigated the structural properties of the Aβ homodimer and pentamer. , Furthermore, we performed two-dimensional infrared (2D IR) analysis to characterize the H-bond and charge networks in a dipeptide model for different states of histidine tautomers . On the basis of the theoretical studies, the histidine tautomerism hypothesis was proposed for protein misfolding.…”
Section: Introductionmentioning
confidence: 99%